Coordination of a Phosphine‐Tethered Aminoborane to Group 10 Metals - Tiddens, Martine R.; Kappé, Bram T.; Smak, Tom J.; Lutz, Martin; Moret, Marc‐Etienne (Chemistry : a European journal, 2024)
While π‐complexes of C=C bonds are ubiquitous in organometallic chemistry, analogous complexes of the isoelectronic but strongly polarized B=N double bond of aminoboranes are extremely scarce. To address this gap, a diphosphine‐aminoborane ligand (PhDPBAiPr) is introduced and its coordination with group 10 metals is investigated. The B=N bond does not coordinate to the metal in Pt(0) and Pd(II) complexes. In contrast, side‐on coordination of the B=N bond is observed in the Ni(0) complex (PhDPBAiPr)Ni(NCPh), and the X‐ray crystal structure reveals B−N bond elongation compared to the free ligand. The choice of co‐ligand strongly influences the presence or absence of side‐on coordination at Ni(0) as evidenced by NMR spectroscopy. While the B=N π‐complex is geometrically similar to C=C analogues, a bonding analysis reveals that the interaction of the B=N motif with the electron‐rich Ni(0) center is best described as 3c4e hyperbond, in which Ni and N are competing for the empty orbital on B. The synthesis and coordination chemistry of a diphosphine‐aminoborane ligand to group 10 metals is reported, affording a rare aminoborane π‐complex of Ni(0). The bonding situation is best described as a 3‐center‐4‐electron bond where the Ni and N atoms compete for an accepting orbital on boron. In contrast with isoelectronic olefin π‐complexes, the metal‐ligand bond is tenuous and the B=N ligand is therefore easily displaced.